More Women in Tech? Evidence from a Field Experiment Addressing Social Identity - Lucía Del Carpio; Maria Guadalupe (Institute of Labor Economics (IZA), 2018)
This paper investigates whether social identity considerations-through beliefs and normsdrive women's occupational choices. We implement two field experiments with potential applicants to a five-month software-coding program offered to women from low-income backgrounds in Peru and Mexico. When we correct the perception that women cannot succeed in technology by providing role models, information on returns and access to a female network, application rates double and the self-selection patterns change. Analysis of those patterns suggests that identity considerations act as barriers to entering the technology sector and that some high-cognitive skill women do not apply because of their high identity costs.
Keywords: J16; J24; D91; 330; occupational segregation; social norms; identity